Pluriversal Literacies: Affect and Relationality in Vulnerable Times. Issue 2 (6th April 2020) - Perry, Mia
Abstract: Through a consideration of literacies in theory and international policy, this article pushes at the edges of existing frameworks of functional and sociocultural literacies. In critique of existing policy directives, the author explores an approach to literacy that engages in the affective and posthuman relationality of human and environment and in the plurality of literacies globally that are overshadowed in prevailing models of literacy education. The author was motivated by a commitment to literacy education responsive to a world that is unsustainable in its current practices, to a world that faces increasing fragmentation and vulnerability (socially and ecologically) while certain types of expertise, technologies, and global infrastructures continue to proliferate. As a mainstay of education and a tool of social change, literacies are inseparable from policy and practices of sustainability, equity, and development. Pluriversality is a concept emerging from decolonial theory that provides a counternarrative to contemporary Northern assumptions of the universal. Building on a history of ideas around pluriversality gives sociopolitical and ecological momentum to affect and relationality in literacy studies. The author challenges normative constructions of literacy education as Eurocentric and neocolonial, effectively supporting a pedagogy that normalizes certain practices and people and, by extension, sustains inequity and environmental degradation. Through interwoven research projects, the author highlights the contentious aspects of functional and sociocultural approaches to literacy and the possibilities of moving beyond them. In doing so, the author describes and demonstrates the practical and political implications of affect theory and relationality in literacies education in a plural anthropocenic world.